THE EFFECT OF TRAINING METHODS AND MOTIVATION ON THE SKILLS TO PLAY FOOTBALL AT SSB TUNAS JAYA PLAYERS JAMBI CITY - Andi Gunawan (Program Pascasarjana Universitas Negeri Jakarta, 2021)
Based on the observations in the field, it showed that of SSB Tunas Jaya Jambi often fail when they were doing football skills. Besides, the exercise method was not systematic and football skill was still not perfect. Therefore, this study aimed at observing the effect of commando style exercise methods, exploration style exercise method and practicing motivation toward football skill. This was a quasi-experimental research. The populations of the research were the athletes of Tunas Jaya SSB Jambi that consisted of 90 people. The group of samples was taken through purposive sampling. The samples treathment in this research were 48, after they were divided into groups in which 27% was related to the high level of practicing motivation and 27% was related to low level of practicing motivation. The instruments of practicing motivation were measured through questionnaires and football skill was measured through test consisting of four forms of test, such as dribbling, short passed, shooting at the goal, and ball control. The data obtained were analyzed by using the analysis of variance (ANOVA) of two lines and tukey test. The results of this research indicate that: (1) commando style exercise methods is more effectively used to enhance the football skill than exploration style exercise methods, (2) there is interaction between the method of exercises and practicing motivation toward football skill, (3) in the high level of practicing motivation, commando style exercise method is more effective than the exploration style exercise methods to enhance football skills, and (4) in the low level of practicing motivation, exploration style exercise method is more effective than commando style exercise methods to enhance the football skill